Academic metrics and publication history of presenters at the American Shoulder and Elbow Surgeons closed annual conferences from 2016 to 2022 - Aaron M. Atlas, DO, MS; Christina Montesano, BS; Brandon Klein, DO, MBA; John Grossi, BS; Kyle Cullin, DO; Randy M. Cohn, MD (JSES Reviews, Reports, and Techniques, 2025)
Background: The American Shoulder and Elbow Surgeons (ASES) holds annual educational meetings to highlight new advances in the field of shoulder and elbow surgery. This study aims to assess the academic metrics of lecturers, ICL instructors, and moderators at ASES annual meetings. Methods: A review of selected presenters (lecturers, ICL instructors, and moderators) at ASES annual meetings from 2016 to 2022 was performed. Presentation topics were categorized into ten topic-specific content areas. Presenters' Hirsch index (H-index), number of topic-specific publications, and field-weighted citation impact (FWCI) were examined to assess academic metrics. Results: Overall, 348 presenters were evaluated. 76.6% of presentations were provided by physicians with at least 1 prior topic-specific publication. Lecturers and symposium moderators had the highest average proportion of presenters with previous topic-specific publications (81.5%), followed by ICL instructors (72.7%). The most commonly presented content topics included arthroplasty techniques (16.8%), followed by rotator cuff tears (15.9%) and surgical complications (12.4%). Infections-prophylaxis and treatment was the least presented topic (3.1%). Lecturers discussing infection held the highest average FWCI (2.55), while elbow injuries had the highest average H-index (59.6). ICL instructors discussing rotator cuffs had the highest average FWCI (4.7), while ICL instructors on biologics had the highest H-index (58.0). Symposium moderators on infection held the highest average FWCI (2.8), while those discussing nonclinical/orthopedic topics had the highest average H-index (55). Conclusion: A high percentage of ASES presenters had previous topic-specific publications as well as distinguishable H-indices and FWCI. Speakers at ASES annual meetings are academically accomplished within the field of shoulder and elbow surgery.